PENGARUH PENGENCERAN DAN PENGADUKAN TERHADAP PRODUKSI BIOGAS PADALIMBAH INDUSTRI KECIL PENGASAPAN IKAN DENGAN MENGGUNAKAN EKSTRAK RUMEN SAPI SEBAGAI STARTER - Pranata Anggakara; Sudarno Sudarno; Irawan Wisnu Wardhana (Jurnal Teknik Lingkungan, 2013)
Fish waste is a problem arising from the activities of the fishing industry. In General, fish waste containing organic compounds are high, therefore, sewage treatment needs to be done to minimize waste. One of the technology for processing waste, namely by means of the creation of biogas by anaerobic. The advantage of this treatment is to produce a little mud than reprocessing in aerobics. This research aims to analyze the influence of addition of rumen of biogas production, the influence of dilution of biogas production and biogas production influence of stirring. This research was conducted in laboratory scale by using a typical analysis for digester capacity 500 mL. The sample used is a waste of the Stingray fish smoking industry, using a sample of mashed and not mashed as well as extracts of bovine rumen as a starter. Water used for dilution in the study is well water with salinity levels of 7.6 ppt. on variable dilution, yield the most high biogas contained on the dilution of 37.5 mL. For the addition of rumen biogas results higher than without the rumen. Stirring 3 times more effective for producing biogas is higher compared to without stirring and stirring 1 time.